Structural and photophysical properties of coordination networks combining [Ru(bipy)(CN)4]2- anions and lanthanide(III) cations: rates of photoinduced Ru-to-lanthanide energy transfer and sensitized near-infrared luminescence. - Davies, G; Pope, S; Adams, H; Faulkner, S; Ward, MD (2005)
Co-crystallization of K2[Ru(bipy)(CN)4] with lanthanide(III) salts (Ln = Pr, Nd, Gd, Er, Yb) from aqueous solution affords coordination oligomers and networks in which the [Ru(bipy)(CN)4]2- unit is connected to the lanthanide cation via Ru-CN-Ln bridges. The complexes fall into two structural types: [{Ru(bipy)(CN)4}2{Ln(H2O)m}{K(H2O)n}] x xH2O (Ln = Pr, Er, Yb; m = 7, 6, 6, respectively), in which two [Ru(bipy)(CN)4]2- units are connected to a single lanthanide ion by single cyanide bridges to give discrete trinuclear fragments, and [{Ru(bipy)(CN)4}3{Ln(H2O)4}2] x xH2O (Ln = Nd, Gd), which contain two-dimensional sheets of interconnected, cyanide-bridged Ru2Ln2 squares. In the Ru-Gd system, the [Ru(bipy)(CN)4]2- unit shows the characteristic intense (3)metal-to-ligand charge transfer luminescence at 580 nm with tau = 550 ns; with the other lanthanides, the intensity and lifetime of this luminescence are diminished because of a Ru --> Ln photoinduced energy transfer to low-lying emissive states of the lanthanide ions, resulting in sensitized near-infrared luminescence in every case. From the degree of quenching of the Ru-based emission, Ru --> Ln energy-transfer rates can be estimated, which are in the order Yb (k(EnT) approximately 3 x 10(6) sec(-1), the slowest energy transfer) < Er < Pr < Nd (k(EnT) approximately 2 x 10(8) sec(-1), the fastest energy transfer). This order may be rationalized on the basis of the availability of excited f-f levels on the lanthanide ions at energies that overlap with the Ru-based emission spectrum. In every case, the lifetime of the lanthanide-based luminescence is short (tens/hundreds of nanoseconds, instead of the more usual microseconds), even when the water ligands on the lanthanide ions are replaced by D2O to eliminate the quenching effects of OH oscillators; we tentatively ascribe this quenching effect to the cyanide ligands.